4(sin⁴30°+cos²60°)-3(cos²45°-sin²90°)-sin²60°​

Question

4(sin⁴30°+cos²60°)-3(cos²45°-sin²90°)-sin²60°​

in progress 0
Delilah 1 month 2021-08-18T08:03:12+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-08-18T08:04:52+00:00

    Answer:

    hey mate please mark me as barinliest

    Step-by-step explanation:

    Given :

    4(sin⁴ 30° + cos² 60°) – 3(cos² 45° – sin² 90° ) – sin² 60°  

    = 4[(1/2)⁴ +(1/2)²] −  3[(1/√2)² −1) −(√3/2)²  

    [sin 30°= ½ ,   cos 60°= ½ , cos 45° = 1/√2, sin 90° = 1 , sin 60°= √3/2]

    = 4[1/16 + ¼] –  3[½ – 1] – 3/4

    = 4 [ (1 + 1×4)/16] – 3 [(1 – 1×2)/2] – ¾

    [By taking L.C.M of  denominator]

    = 4 [ (1+ 4)/16] –  3 [(1 – 2)/2] – 3/4

    = 4[5/16] –  3 [ – 1/2 ] – 3/4

    = 5/4 + 3/2 – ¾

    = 5/4 – ¾ + 3/2

    [By rearranging  the terms]

    = (5 – 3)/4 + 3/2

    = 2/4 + 3/2

    = ½ + 3/2

    = (1+3)/2

    = 4 /2  = 2  

    4(sin⁴ 30° + cos² 60°) – 3(cos² 45° – sin² 90° ) – sin² 60° = 2

    Hence, 4(sin⁴ 30° + cos² 60°) – 3(cos² 45° – sin² 90° ) – sin² 60°

    HOPE THIS ANSWER WILL HELP YOU…

    0
    2021-08-18T08:05:04+00:00

    Answer:

    2

    Step-by-step explanation:

    4(sin⁴30°+cos²60°)-3(cos²45°-sin²90°)-sin²60°​

    =4((\frac{1}{2})⁴+3((\frac{1}{\sqrt{2} })² – (1)

    =\frac{(4)(5)}{16}+ \frac{3}{2}\frac{3}{4}

    =\frac{5+6-3}{4}

    =\frac{8}{4} =2

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )